تحقيق كتب الأحكام، والتمني، والاعتصام من كتاب حواش على صحيح البخاري، لعبد القادر الفاسي (Journal of Academic Research, 2026)
This study presents a critical edition of selected sections titled “Kitāb al-Aḥkām,” “Kitāb al-Tamannī,” and “Kitāb al-Iʿtiṣām” from the work “Ḥawāshī ʿalā Ṣaḥīḥ al-Bukhārī” by the scholar ʿAbd al-Qādir al-Fāsī, accompanied by an analytical examination of his intellectual profile and methodology.In the first section, the researcher introduces the author, highlighting his scholarly standing and emphasizing the intellectual and Sufi background that shaped his thought. The second section is devoted to the critical editing of the manuscript texts, where they are transcribed into modern orthography in accordance with contemporary writing conventions, alongside a careful comparison of the available manuscript copies.The study also includes the verification of the cited ḥadīths, proper documentation and attribution of quoted statements to their original sources, and the identification of both prominent and lesser-known figures mentioned in the marginalia. Furthermore, explanatory notes and clarifications are provided for issues requiring further elaboration.